Femtosecond laser plasma: review of investigation and calculational model - Bugrov, N.; Kholod, S.; Zaharov, N. (Вопросы атомной науки и техники, 2005)
Review of experimental and theoretical investigation of physical processes in femtosecond laser plasma is presented. Such effects, as X-ray and electric-magnetic wave emission, high energy electron and ion beams are described. It isshown that ultrashort laser pulse with duration comparable to period of wave oscillation (lessthan a few femtoseconds) is absorbing by inner electronsin contrast to absorption of more lasting laser pulses by outer electrons. The problem of mathematical modelling of these processes and corresponding computer code development is observed. Technological applications, such as production of high power X-ray and particles plasmassources, laser precision shaping and machining of different materials are discussed. Представлено огляд експериментальних і теоретичних досліджень фізичних процесів, що відбуваються у фемтосекундній лазерній плазмі. Описано такі ефекти, як рентгенівське й електромагнітне випромінювання, високоенергетичні електронні й іонні пучки. Показано, що ультракороткий лазерний імпульс тривалістю, порівнянною з періодом коливання хвилі (меншою ніж декілька фемтосекунд), поглинається внутрішніми електронами, на відміну від більш тривалих імпульсів, що поглинаються зовнішніми електронами. Розглянуто задачу математичного моделювання цих процесів і створення відповідного комп'ютерного коду. Обговорено технологічні аспекти, такі, як створення могутніх джерел рентгенівського випромінювання і плазми, формування лазерного пучка й обробка різних матеріалів. Представлен обзор экспериментальных и теоретических исследований физических процессов, происходящих в фемтосекундной лазерной плазме. Описаны такие эффекты, как рентгеновское и электромагнитное излучение, высокоэнергетичные электронные и ионные пучки. Показано, что ультракороткий лазерный импульс длительностью, сравнимой с периодом колебания волны (меньшей, чем несколько фемтосекунд), поглощается внутренними электронами, в отличие от более продолжительных импульсов, которые поглощаются внешними электронами. Рассмотрена задача математического моделирования этих процессов и создания соответствующего компьютерного кода. Обсуждены технологические аспекты, такие, как создание мощных источников рентгеновского излучения и плазмы, формирование лазерного пучка и обработка различных материалов.